1998
DOI: 10.1128/iai.66.2.451-461.1998
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4-Dependent Immunoglobulin G1 Isotype Switch in the Presence of a Polarized Antigen-Specific Th1-Cell Response to the Trypanosome Variant Surface Glycoprotein

Abstract: This study examines B-cell immunoglobulin (Ig) class-switching events in the context of parasite antigen-specific Th-cell responses in experimental African trypanosomiasis. Inbred mice were infected withTrypanosoma brucei rhodesiense, and the coordinate stimulation of Th-cell cytokine responses and B-cell responses to the trypanosome variant surface glycoprotein (VSG) was measured. The cytokines produced by T cells in response to VSG, at both the transcript and protein levels, were gamma interferon and interle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 68 publications
2
23
0
3
Order By: Relevance
“…These results clearly show that there was no correlation between the frequency of cytokine-secreting cells and the actual amount of cytokine secretion by the cells. This is consistent with the recent findings of Schopf et al (1998) that showed that although IL-4-secreting cells in the spleens of T. brucei rhodesiense-infected mice were readily demonstrable by ELISPOT, no detectable amount of IL-4 protein was measurable in culture fluids of splenocytes from these mice.…”
Section: Levels Of Cytokine Protein In Cultures Of Splenocytes From Isupporting
confidence: 92%
See 2 more Smart Citations
“…These results clearly show that there was no correlation between the frequency of cytokine-secreting cells and the actual amount of cytokine secretion by the cells. This is consistent with the recent findings of Schopf et al (1998) that showed that although IL-4-secreting cells in the spleens of T. brucei rhodesiense-infected mice were readily demonstrable by ELISPOT, no detectable amount of IL-4 protein was measurable in culture fluids of splenocytes from these mice.…”
Section: Levels Of Cytokine Protein In Cultures Of Splenocytes From Isupporting
confidence: 92%
“…However, this possibility seems less likely since similar cultures of splenocytes from BALB/c mice produced significant amounts of IL-4 ( Figure 3a). Similar observation has been made in resistant B10.BR mice infected with T. brucei rhodesiense wherein IL-4-secreting cells were readily demonstrable in the spleens whereas no measurable amount of IL-4 was detected in splenocyte culture fluids even in the presence of blocking anti-IL-4 receptor antibodies (Schopf et al 1998). Similarly, although greater numbers of IL-4-than IFN-g-secreting splenocytes (approximate ratio, 2 : 1) were detected on day 6 in the BALB/c mice, the ratio of IL-4 to IFN-g protein secreted in culture was dramatically different (IL-4:IFN-g ¼ 1 : 85).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A major shift in this paradigm was provided by studies that demonstrated relative resistance to infection was linked functionally and genetically to VSG-specific CD4 + Th1 cell responses. [1][2][3][4][5][6] Further studies revealed that Th1 cells were a major source of the cytokine interferon-gamma (IFN-γ) that was linked to relative resistance 7 ; IFN-γ served to activate macrophages in host tissues, with the result that a number of cytotoxic factors are released that are capable of killing trypanosomes in a variant-nonspecific manner ( Figures 1 and 2). 6,[8][9][10][11] Thus, the ability to selectively induce Th1 cell responses to trypanosome antigens may have benefits for host resistance.…”
Section: Vsgs As Immunological Targets In Trypanosoma Brucei Spp Inmentioning
confidence: 99%
“…This occurred in the presence of IFNγ and IL-2, but the absence of IL-4 and IL-5. However, when repeating these measurements in IL-4 knock-out mice, a significant decrease in IgG1 titers was observed, indicating a role for this cytokine in the regulation of B cell activity, independent of antigen specific Th1 or Th2 cells (78). In the same context, IgG switching was also observed in experimental T brucei infections in both WT and nu/nu BALB/c mice, with IgG1, IgG2a, IgG2b, and IgG3 isotype antibodies being produced independent of conventional T cell help (79).…”
Section: Trypanosomes Avoid Antibody-mediated Killing By Destruction mentioning
confidence: 94%